Cash flow accounting : international uses and abuses - Donleavy, G. D. (G. Douglas) (London : New York : Routledge, 1994)
Cash Flow Accounting explores for the first time the usefulness of the funds flow statement and its replacement by the cash flow statement.
The book begins with an analysis of accounting history and of the role of accountants in advising investors and creditors. It then goes on to review both the funds flow statement and the cash flow statement in terms of their history, geographical spread, usefulness to investors and lenders and their incremental information content in a global context. The discussion explores whether the new cash flow statement satisfies the aspirations of the old funds statement better than the original statement did.
Readers are invited to examine actual funds and cash flow statements. Cash flow accounting fundamentalism is also critically examined along with the contribution of information overload theories in helping us understand the size of the gap between the actual and potential usefulness of accounting statements. The book concludes with suggestions as to how future studies of accounting usefulness could contribute to enhancing the role of accounting as the 'language of business'.
Firmly set in a modern, global context, this volume will be invaluable for advanced students of financial accounting, accounting theory, and international accounting. Practising accountants will also find the analysis of real-world accounting useful and thought provoking.
1. The history and usefulness of accounting -- 2. Information content of company accounts to investors -- 3. Information content of company accounts to lenders -- 4. Evolution of the funds and cash flow statements -- 5. Global reach of the funds statement -- 6. Cash flow statements -- 7. Funds statements cases -- 8. Cash flow extremism -- 9. Information load and accounting statements -- 10. Conclusion.
Includes bibliographical references (p. [255]-294) and index.
Keywords: Cash flow -- Accounting